The Influence of Customer Experience and Product Quality to Passenger Satisfaction on Kuliner Kereta in PT. Kereta Api Indonesia - Puspitasari, Dyah Ayu Kunthi (Universitas Syiah Kuala, 2023)
PT. Kereta Api Indonesia (KAI) continues to innovate in developing its company. One of the development programs is #KulinerKereta, a program that offers culinary sensations on the train. Each route will have its menu so that one route with another itinerary will have a different culinary menu. The purpose of this research is to find out whether consumer experience and product quality (food) will have an impact on passenger satisfaction in enjoying culinary delights on the train. This study uses quantitative methods with primary data collection techniques, namely distributing questionnaires. Questionnaires were distributed to 100 respondents, namely consumers who did culinary tours on the train. The SmartPLS application is used to test the data in this study. Based on the results of data processing in this study, shows that there is a positive influence between consumer experience and customer satisfaction and product quality (food) also has a positive influence on passenger satisfaction.